2018
DOI: 10.1080/03007995.2018.1525344
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of postprandial hyperglycemic episodes in people with diabetes: impact on daily functioning

Abstract: Increased severity and frequency of aPPHG episodes in patients with insulin-treated diabetes is associated with greater burden and experience of symptoms, and can negatively impact daily functioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…12 In a large study of patients with type 1 diabetes and type 2 diabetes (n = 1200), Heller et al found that increased severity and frequency of acute postprandial hyperglycemia is associated with greater burden and experience of symptoms and can negatively impact daily functioning of patients. 13 CGM-based measures such as TIR provide additional information that patients can use to understand how their insulin, meals, and exercise affect glycemic control. TIR was also identified as one of the ''biggest drivers of improved diabetes management and mindset,'' and ranked only behind food choice as having the biggest impact on daily life in a survey of 3461 people with type 1 diabetes or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…12 In a large study of patients with type 1 diabetes and type 2 diabetes (n = 1200), Heller et al found that increased severity and frequency of acute postprandial hyperglycemia is associated with greater burden and experience of symptoms and can negatively impact daily functioning of patients. 13 CGM-based measures such as TIR provide additional information that patients can use to understand how their insulin, meals, and exercise affect glycemic control. TIR was also identified as one of the ''biggest drivers of improved diabetes management and mindset,'' and ranked only behind food choice as having the biggest impact on daily life in a survey of 3461 people with type 1 diabetes or type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Early (1 h) post-prandial hyperglycemic spikes emerge as better determinant of metabolic dysregulation and vascular alterations than later (2 h) glycemic values (3). Post-prandial hyperglycemia also worsens quality of life and is associated with loss of productivity (4)(5)(6). Therefore, mitigating post-prandial hyperglycemia is one of the aims of T1D glycemic management.…”
Section: Introductionmentioning
confidence: 99%